Development of Biology Learning Devices With Problem Based Learning In Biodiversity Materials In The Middle School Of The State 1 Batudaa Pantai - Yusuf, Frida Maryati; Mardin, Herinda; Latjompoh, Masra (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2022)
This study aims to produce problem-based learning biology learning devices on biodiversity material in class X. This research is research and development to adapt the 4-D development model by Thiagarajan and Semmel (1973), which consisted of the defining stage, the design stage The development stage, and the dissemination stage. This development research includes the development of learning devices consisting of Lesson Plans (RPP), Student Worksheets (LKPD), and Learning Outcomes Test (THB) on Biodiversity class X material in high schools. The data collected through non-test techniques and test techniques and data analyzed through descriptive statistical analysis, which consists of: (1) validity data analysis (2) practical data analysis (3) effectiveness data analysis (4) Analysis of student response data (5) Analysis of learning outcome test data. The results of validation and testing indicate that the developed learning tools meet the criteria of validity, practicality and effectiveness.